Biodiversity and ecology of microorganisms in high pressure membrane filtration systems. (1st April 2020) - de Vries, Hendrik J.; Stams, Alfons J.M.; Plugge, Caroline M.
Abstract: High-pressure membrane filtration (reverse osmosis and nanofiltration) is used to purify different water sources, including wastewater, surface water, groundwater and seawater. A major concern in membrane filtration is the accumulation and growth of micro-organisms and their secreted polymeric substances, leading to reduced membrane performance and membrane biofouling. The fundamental understanding of membrane biofouling is limited despite years of research, as the means of microbial interactions and response to the conditions on the membrane surface are complicated. Here, we discuss studies that investigated the microbial diversity of fouled high-pressure membranes. High-throughput amplicon sequencing of the 16S rRNA gene have shown that Burkholderiales, Pseudomonadales, Rhizobiales, Sphingomonadales and Xanthomonadales frequently obtain a high relative abundance on fouled membranes. The bacterial communities present in the diverse feed water types and in pre-treatment compartments are different from the communities on the membrane, because high-pressure membrane filtration provides a selective environment for certain bacterial groups. The biofilms that form within the pre-treatment compartments do not commonly serve as an inoculum for the subsequent high-pressure membranes. Besides bacteria also fungi are detected in the water treatment compartments. In contrast to bacteria, the fungal community does not change much throughout membrane cleaning. The stable fungal diversity indicates that they are more significant in membrane biofouling than previously thought. By reviewing the biodiversity and ecology of microbes in the whole high pressure membrane filtration water chain, we have been able to identify potentials to improve biofouling control. These include modulation of hydrodynamic conditions, nutrient limitation and the combination of cleaning agents to target the entire membrane microbiome. Graphical abstract: Image 1 Highlights: Different membrane cleaning agents select for distinct bacterial communities. The role of fungi in membrane biofouling has been underestimated. Microbial EPS and appendages prevent removal by frictional fluid forces. Membrane filtration provides a selective environment for bacteria but not for fungi. Members of interkingdom biofilms benefit from cross-protection.